The relative impact of school‐wide positive behavior support on teachers' perceptions of student behavior across schools, teachers, and students. Issue 2 (13th November 2018) - Wienen, Albert W.; Reijnders, Inge; van Aggelen, Marleen H.; Bos, Elske H.; Batstra, Laura; de Jonge, Peter
Abstract: School‐wide positive behavior support (SWPBS) is a systemic approach for implementing a proactive schoolwide discipline and for improving students' academic and behavioral outcomes by targeting the school's organizational and social culture. With a multilevel approach, the present study evaluates the relative effectiveness of SWPBS on teachers' perceptions of the student behavior ( N = 3, 295) across schools, teachers, and children using a multilevel approach. We assessed teacher perception of student problem behavior five times during a 3‐year implementation of SWPBS in 23 Dutch schools. Multilevel analyses not only revealed a small increase in perceived prosocial behavior and a small decrease in problems with peers, but also different effects across children, teachers, and schools. Effects were stronger for girls and for students with higher severity of perceived problems at baseline. At teachers' level, higher mean baseline severity of perceived problems was associated with the reduced impact of SWPBS on perceived emotional problems and problems with peers. At the school level, effects were stronger for regular schools as compared with special needs schools.